The Influence of Inversive Constructions in the Translation of French and Uzbek Artworks - Туйбоева, Шахноза (Центр Научных Публикаций (buxdu.uz), 2024)
This article explores the role and significance of inversion in the translation of fiction. Inversion is a variation of Word Order used to preserve the meaning and stylistic characteristics of the original text. The study is based on translations of fiction in French and Uzbek. The article analyzes the types of inversion, the reasons for its application and the effect on the quality of translation. The results of the study show that inversion plays an important role in the translation process and is an effective tool for translators.